2020
DOI: 10.3390/rs12162613
|View full text |Cite
|
Sign up to set email alerts
|

An Operational Split-Window Algorithm for Retrieving Land Surface Temperature from Geostationary Satellite Data: A Case Study on Himawari-8 AHI Data

Abstract: An operational split-window (SW) algorithm was developed to retrieve high-temporal-resolution land surface temperature (LST) from global geostationary (GEO) satellite data. First, the MODTRAN 5.2 and SeeBor V5.0 atmospheric profiles were used to establish a simulation database to derive the SW algorithm coefficients for GEO satellites. Then, the dynamic land surface emissivities (LSEs) in the two SW bands were estimated using the Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER) Global Emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 98 publications
0
6
0
Order By: Relevance
“…The AGRI is very similar to the Advanced Himawari Imager (AHI) onboard the Japanese geostationary meteorological satellites Himawari-8 and -9 [1], and the Advanced Baseline Imager (ABI) onboard the U.S. Geostationary Operational Environmental Satellite (GOES)-R series [2]. These newgeneration geosynchronous imagers are important for numerical data assimilation and weather forecasting [3][4][5][6][7], disaster prevention and mitigation [8,9], as well as atmosphere and surface parameter retrievals [10][11][12][13].…”
Section: Introductionmentioning
confidence: 83%
“…The AGRI is very similar to the Advanced Himawari Imager (AHI) onboard the Japanese geostationary meteorological satellites Himawari-8 and -9 [1], and the Advanced Baseline Imager (ABI) onboard the U.S. Geostationary Operational Environmental Satellite (GOES)-R series [2]. These newgeneration geosynchronous imagers are important for numerical data assimilation and weather forecasting [3][4][5][6][7], disaster prevention and mitigation [8,9], as well as atmosphere and surface parameter retrievals [10][11][12][13].…”
Section: Introductionmentioning
confidence: 83%
“…Due to the lack of official AHI LST products, a couple of split-window (SW) algorithms have been developed [64][65][66]. The SW algorithm assumed that the land surface emissivity (LSE) was known in advance, yet accurate LSE was extremely hard to obtain.…”
Section: Clear-sky Ahi Lst Retrievalmentioning
confidence: 99%
“…Several studies have shown that different atmospheric reanalysis products have similar accuracy for LST retrieval [57]- [59]. Furthermore, reanalysis products could provide global atmospheric information with high temporal resolution than satellite retrievals and may be more suitable for LST retrieval [48].…”
Section: B Era5 Atmospheric Reanalysis Datamentioning
confidence: 99%